Artificial Intelligence in Multicultural Islamic Education: Opportunities, Challenges, and Ethical Considerations - M Mahmudulhassan; M Muthoifin; Sazirul Begum (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
This study investigates the integration of artificial intelligence (AI) cutting-edge technology, with Islamic education, and the opportunities, difficulties, ethics, and moral dilemmas related to Islamic education. Artificial intelligence (AI) has become a revolutionary force in many industries, and interest in its potential applications in education has grown usefully. The paper’s objective is to shed light on how artificial intelligence (AI) can be applied to improve Islamic education’s accessibility and quality while upholding the community’s core beliefs. The study analyzes Artificial Intelligence in Islamic Education: Opportunities, Challenges, and Ethical Considerations through the literature study method, especially on online sources. The results show that if we can apply artificial intelligence with Ethical Considerations, it will be beneficial in this digital age to improve the accessibility of Islamic education.